PENGARUH PADAT TEBAR YANG BERBEDA TERHADAP PERTUMBUHAN DAN TINGKAT KELANGSUNGAN HIDUP BENIH IKAN BAWAL BINTANG (Trachinotus blochii) - Astutiwati (Program Studi Ilmu Perikanan, Fakultas Ilmu dan Teknologi Hayati, Universitas Teknologi Sumbawa, 2025)
Silver pompano fish has great potential for widespread development. This study aims to determine the optimal stocking density that supports the growth and survival rates of silver pompano (Trachinotus blochii). The research was conducted from June 23, 2023, to July 23, 2023, at the Lombok Marine Aquaculture Center, located in Sekotong Village, Sekotong District, West Lombok Regency, West Nusa Tenggara Province. The method used was an experimental approach with a Completely Randomized Design (CRD), consisting of five treatments, each repeated five times, resulting in 25 experimental units. The treatments were as follows: P1 = 5 fish/10 liters, P2 = 15 fish/10 liters, P3 = 25 fish/10 liters, P4 = 35 fish/10 liters, and P5 = 45 fish/10 liters. The results showed that stocking density did not affect the growth of silver pompano but had an impact on its survival rate. The average growth data revealed that a density of 15 fish/10L (P2) produced the highest final weight of 3.12 g, while a density of 5 fish/10L (P1) resulted in the lowest final weight of 2.958 g.